The Effect of Positive End Expiratory Pressure on Reduction of Respiratory Complications during and after the Surgery in Patients undergoing Laparoscopic Bariatric Surgery - Heidar Karimi; Parvin Sajedi (مجله دانشکده پزشکی اصفهان, 2020)
Background: This study aimed to determine the effect of positive end expiratory pressure (PEEP) on reduction of respiratory complications during and after the surgery in patients undergoing laparoscopic bariatric surgery.